2007
DOI: 10.1105/tpc.106.049585
|View full text |Cite
|
Sign up to set email alerts
|

The PP2C-Type Phosphatase AP2C1, Which Negatively Regulates MPK4 and MPK6, Modulates Innate Immunity, Jasmonic Acid, and Ethylene Levels inArabidopsis

Abstract: Wound signaling pathways in plants are mediated by mitogen-activated protein kinases (MAPKs) and stress hormones, such as ethylene and jasmonates. In Arabidopsis thaliana, the transmission of wound signals by MAPKs has been the subject of detailed investigations; however, the involvement of specific phosphatases in wound signaling is not known. Here, we show that AP2C1, an Arabidopsis Ser/Thr phosphatase of type 2C, is a novel stress signal regulator that inactivates the stress-responsive MAPKs MPK4 and MPK6. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
317
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(358 citation statements)
references
References 87 publications
20
317
0
1
Order By: Relevance
“…On the other hand, lack of MPK3 increases basal susceptibility, as previously reported (Ren et al, 2008), but does not significantly affect elicitor-induced resistance. Consistently, simultaneous dephosphorylation of MPK3 and MPK6 in transgenic plants overexpressing the Arabidopsis MAPK Ser/Thr phosphatase AP2C1 (Schweighofer et al, 2007) impairs both basal and induced resistance to B. cinerea, recapitulating the phenotypes observed in single mapk mutants.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…On the other hand, lack of MPK3 increases basal susceptibility, as previously reported (Ren et al, 2008), but does not significantly affect elicitor-induced resistance. Consistently, simultaneous dephosphorylation of MPK3 and MPK6 in transgenic plants overexpressing the Arabidopsis MAPK Ser/Thr phosphatase AP2C1 (Schweighofer et al, 2007) impairs both basal and induced resistance to B. cinerea, recapitulating the phenotypes observed in single mapk mutants.…”
mentioning
confidence: 55%
“…A previous report demonstrated that MPK6 can be dephosphorylated by the Arabidopsis PP2C Ser/Thr protein phosphatase AP2C1 (Schweighofer et al, 2007). The expression of AP2C1 gene is up-regulated in response to several MAMPs, as shown by publicly available microarray data (Supplemental Fig.…”
Section: Elicitor-induced Phosphorylation Of Both Mpk3 and Mpk6 Is Prmentioning
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, the speed with which SIPK activity levels decrease in AZ following simulated herbivory (W1OS) suggests that the negative regulation of SIPK is stronger in AZ than in UT. A recent study in Arabidopsis has shown that a phosphatase, AP2C1, might be responsible for this negative regulation (Schweighofer et al, 2007). .…”
Section: Natural Variation In Herbivore-induced Signaling Eventsmentioning
confidence: 99%
“…Additional support indicating that MPK4 positively regulates the JA pathway comes from investigation of AP2C1, an Arabidopsis Ser/ Thr phosphatase of type 2C, that is a novel stress signal regulator that inactivates MPK4. ap2c1 mutants produce significantly higher amounts of JA upon wounding and are more resistant to phytophagous mites (Schweighofer et al, 2007).…”
mentioning
confidence: 99%